PENGARUH MIRROR THERAPY TERHADAP UJI KEKUATAN OTOT PASIEN STROKE NON HEMORAGIK DI RSUD CURUP TAHUN 2022 - Dika Putri Robinson; Hartian Med Pansori; Dilfera Hermiati (Universitas Pahlawan Tuanku Tambusai, 2023)
Stroke has caused the death of 130,000 people and is the number 5 leading cause of death. In Indonesia, in 2018 based on a doctor's diagnosis in the population aged 15 years, 10.9%. The purpose of this study was to determine the effect of mirror therapy on muscle strength testing of non-hemorrhagic stroke patients at Curup Hospital in 2022. The method in this study was quantitative, using a quasi-experimental study with a pre post test one group design approach. The sample in this study amounted to 16 respondents who were selected according to the inclusion and exclusion criteria. This study used the Wilcoxon Test statistical test. The results of this study showed that the mean muscle strength before the intervention was 2.19 and the mean muscle strength after the intervention was 3.06. The results of the Wilcoxon Test statistical test obtained a value of value = 0.000 <α = 0.05, H0 was rejected and Ha was accepted, meaning that there was an effect of mirror therapy on the muscle strength test of non-hemorrhagic stroke patients at Curup Hospital in 2022. The conclusion in this study is that mirror therapy can used for non-hemorrhagic stroke patients who have muscle strength problems. Suggestions in this study are patients and families can use mirror therapy as an independent nursing intervention at home. Keywords: Mirror Therapy, Muscle Strength, Non Hemorrhagic Stroke